(untitled) (The Pakistan Development Review, 1988)
The primary objective of this paper is to observe the changing patterns in regional development and to highlight some of the major underlying phenomena. C).1t examination of changes in rank ordering over a short period of time reveals that only moderately developed districts have altered their position in either upward or downward direction. Larkana district moved from sixth to fourth rank, while Tharparkar district regressed considerably from fourth to eighth rank. The exercise will facilitate policy-makers in allocating development resources in districts where the deficiencies are evidently serious. It will also be helpful in locating research areas to determine partkular bottlenecks to development in districts which shifted downward in rank ordering.